PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI PT WOM FINANCE TBK CABANG PALEMBANG - Nina Fitriana; Umi Hasanah; Ria Oktavia (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
The purpose of this research to identify and analyze the influence of leadership style and motivation on employee performance PT Wom Finance Tbk Branch Palembang. The data used are primary and secondary data with a sample of 76 employees. To determine the effect of leadership style and motivation on employee performance PT Wom Finance Open used multiple regression analysis. The research showed that there are significant positit There are significant Influence Style Leadership and Motivation on Employee Performance in PT Wom Finance Palembang. Multiple linear regression equation Y = 9.455 + 0,260 X1 + 0,243 X2 + e. independent variables go hand in hand with the dependent variable means increasing Leadership Styles and Motivation then increased the level of employee performance in PT Wom Finance Palembang. There is a significant Influence Style Leadership and Motivation in Partial (alone) the Employee Performance in PT Wom Finance. The coefficient of determination () of 0.185 indicates that employee performance can be explained by variables leadership style and motivation while the rest Explained other factors not examined. Keyword : Leadership Style, Motivation, Performance